Contrasting edge effect on lianas and trees in a cerrado savanna remnant - van Melis, Juliano; Camargo, Maria Gabriela Gutierrez [UNESP]; Carvalho, Paula Guimarães; Morellato, Leonor Patrícia Cerdeira [UNESP]; Grombone-Guaratini, Maria Tereza (Wiley, 2021)
The ecological impact of lianas in the edges of tropical forest areas is widely recognised; however, the edge influence on the liana community and its relationship with trees in biomes of open vegetation require further evaluation. We compared the following parameters between edges and interiors in a remnant of woody cerrado: (i) the structure of liana and tree communities (abundance, basal area and species richness and composition); (ii) the influence of microenvironmental factors on the abundance and basal area of lianas and trees; and (iii) the relationship between lianas and their host trees. We collected data from plots placed in the edge and interior (100 m distance from the edges) at two cardinal orientations (south and east) of our study site. Our results showed that (i) lianas had greater absolute and per tree host abundances in the edges, while the trees showed greater abundance and lower basal area in the interiors; (ii) there was a positive edge effect on the diversity of lianas but not of trees, with a greater diversity of lianas in the edges, while the interiors showed only a subset of the liana species recorded at the edges; (iii) the edge effect was more pronounced (less tree abundance with a larger basal area and greater abundance of lianas) on the south-facing than on the east-facing edges; and (iv) the microenvironmental factors analysed did not influence the general pattern of abundance and the basal area of trees and lianas. We conclude that, in the remnant of cerrado studied, the edges influenced the liana community, increasing the species richness, abundance and host occupancy. The impact of the greater diversity and abundance of lianas in the edges should be considered in the management and conservation plans of woody cerrado ecosystems.
Keywords: beta diversity; cerrado sensu stricto; climbing plants; edge effect; habitat fragmentation